The Volume and Capacity of Colonoscopy Procedures Performed at New York City Hospitals in 2002 - Jennifer C.F. Leng, MD, MPH; Lorna E. Thorpe, PhD; Gabe E. Feldman, MD, MPH, MBA, MHA; Pauline A. Thomas, MD; Thomas R. Frieden, MD, MPH (Centers for Disease Control and Prevention, 2005)
Introduction Colorectal cancer is the second leading cause of cancer death in New York City. In March 2003, the New York City Department of Health and Mental Hygiene recommended colonoscopy every 10 years as the preferred screening test for adults aged 50 years and older in New York City. To screen all eligible adults in New York City would require that approximately 200,000 colonoscopy exams be performed annually. As part of this recommendation, we evaluated current colonoscopy capacity in New York City hospitals. Methods We surveyed endoscopy suite nursing or administrative staff at all 66 adult acute care hospitals performing colonoscopy in New York City. Data on colonoscopy procedures performed in 2002 were collected between February and June 2003. Results All hospitals and two affiliated clinics responded. The number of hospital-based colonoscopy exams performed in 2002 was estimated to be 126,000. Of these, 53,600 (43%) were estimated to be for screening. Hospitals reported their maximum annual capacity to be 195,200, approximately 69,100 more than current practice. Reported barriers to performing more colonoscopy exams included inadequate suite time and space (31%), inadequate staffing (28%), and insufficient patient referrals (24%). Conclusion In 2003, endoscopy suites at New York City hospitals performed approximately one quarter of the estimated citywide need of 200,000 screening colonoscopies. Procedures conducted in outpatient office settings were not assessed. Most endoscopy suites, particularly private hospitals, reported having the capacity to conduct additional procedures. Hospitals and endoscopy suites should prioritize the development of institutional measures to increase the number of persons receiving screening colonoscopy.